Apparent Digestibility Coefficients of Black Soldier Fly (Hermetia illucens), Yellow Mealworm (Tenebrio molitor), and Blue Bottle Fly (Calliphora vicina) Insects for Juvenile African Catfish Hybrids (Clarias gariepinus × Heterobranchus longifilis) - Zsuzsanna J. Sándor; Vojislav Banjac; Strahinja Vidosavljević; Jenő Káldy; Robert Egessa; Éva Lengyel-Kónya; Rita Tömösközi-Farkas; Zsolt Zalán; Nóra Adányi; Balázs Libisch; Janka Biró (Aquaculture Nutrition)
A digestibility trial was conducted with African catfish hybrid juveniles in order to determine the apparent digestibility coefficients (ADCs) of different nutrients. The experimental diets contained defatted black soldier fly (BSL), yellow mealworm (MW), or fully fat blue bottle fly (BBF) meals, in a 70 : 30 ratio between the control diet and the tested insect meals. The indirect method for the digestibility study was performed using 0.1% yttrium oxide as an inert marker. Fish juveniles of 217.4±9.5 g initial weight were distributed in 1 m3 tanks (75 fish/tank) of a recirculating aquaculture system (RAS), in triplicates, and fed until satiation for 18 days. The average final weight of the fish was 346±35.8 g. The ADCs of the dry matter, protein, lipid, chitin, ash, phosphorus, amino acids, fatty acids, and gross energy for the test ingredients and diets were calculated. A six-month storage test was carried out to evaluate the shelf life of the experimental diets, while the peroxidation and microbiological status of the diets were also assessed. The ADC values of the test diets differed significantly (p<0.001) compared to those of the control for most of the nutrients. Altogether, the BSL diet was significantly more digestible for protein, fat, ash, and phosphorus than the control diet but less digestible for essential amino acids. Significant differences were found between the ADCs of the different insect meals evaluated (p<0.001) for practically all nutritional fractions analyzed. The African catfish hybrids were able to digest BSL and BBF more efficiently than MW, and the calculated ADC values agreed with those of other fish species. The lower ADCs of the tested MW meal correlated (p<0.05) with the markedly higher acid detergent fiber (ADF) levels present in the MW meal and MW diet. Microbiological evaluation of the feeds revealed that mesophilic aerobic bacteria in the BSL feed were 2–3 orders of magnitude more abundant than those in the other diets and their numbers significantly increased during storage. Overall, BSL and BBF proved to be potential feed ingredients for African catfish juveniles and the shelf life of the produced diets with 30% inclusion of insect meal retained the required quality during a six-month period of storage.